Hubungan Keikutsertaan Kelas Ibu Hamil Dengan Tingkat Kecemasan Menghadapi Persalinan Pada Ibu Hamil TM 3 Di Wilayah Kerja Puskesmas Sabrang - Ika Sari Widayanti; Rifzul Maulina (Journal of Innovative and Creativity, 2025)
Introduction: Anxiety during pregnancy poses a significant risk to both maternal and infant health. To address this, pregnant women's classes offer a group learning platform focused on various aspects of health during this period, including childbirth, postpartum care, and newborn care. These classes incorporate practical sessions utilizing the KIA Book. This study specifically aimed to determine the relationship between attending these classes and the anxiety levels of pregnant women in their third trimester as they approach labor. Research Methods: This study employed a quantitative analytic survey with a cross-sectional design. Data was collected from 30 respondents using the HARS questionnaire. For analysis, we used SPSS and performed a Chi-Square test, with a p-value of less than 0.05 indicating statistical significance. Research Results: Our research, conducted on the 30 respondents, yielded a p-value of 0.036 from the Chi-Square test, which is less than 0.05. Conclusion: Based on these findings, we conclude that there is a significant relationship between participation in pregnant women's classes and the level of anxiety experienced by third-trimester pregnant women facing labor at the Sabrang Health Center.